Influence of Protein Glycosylation on Campylobacter fetus Physiology - Duma, Justin; Nothaft, Harald; Weaver, Danielle; Fodor, Christopher; Beadle, Bernadette; Linton, Dennis; Benoit, Stéphane L.; Scott, Nichollas E.; Maier, Robert J.; Szymanski, Christine M. (Frontiers in Microbiology, 2020)
Campylobacter fetus is commonly associated with venereal disease and abortions in cattle and sheep, and can also cause intestinal or systemic infections in humans that are immunocompromised, elderly, or exposed to infected livestock. It is also believed that C. fetus infection can result from the consumption or handling of contaminated food products, but C. fetus is rarely detected in food since isolation methods are not suited for its detection and the physiology of the organism makes culturing difficult. In the related species, Campylobacter jejuni, the ability to colonize the host has been linked to N-linked protein glycosylation with quantitative proteomics demonstrating that glycosylation is interconnected with cell physiology. Using label-free quantitative (LFQ) proteomics, we found more than 100 proteins significantly altered in expression in two C. fetus subsp. fetus protein glycosylation (pgl) mutants (pglX and pglJ) compared to the wild-type. Significant increases in the expression of the (NiFe)-hydrogenase HynABC, catalyzing H2-oxidation for energy harvesting, correlated with significantly increased levels of cellular nickel, improved growth in H2 and increased hydrogenase activity, suggesting that N-glycosylation in C. fetus is involved in regulating the HynABC hydrogenase and nickel homeostasis. To further elucidate the function of the C. fetus pgl pathway and its enzymes, heterologous expression in Escherichia coli followed by mutational and functional analyses revealed that PglX and PglY are novel glycosyltransferases involved in extending the C. fetus hexasaccharide beyond the conserved core, while PglJ and PglA have similar activities to their homologs in C. jejuni. In addition, the pgl mutants displayed decreased motility and ethidium bromide efflux and showed an increased sensitivity to antibiotics. This work not only provides insight into the unique protein N-glycosylation pathway of C. fetus, but also expands our knowledge on the influence of protein N-glycosylation on Campylobacter cell physiology.